2021
DOI: 10.1016/j.heliyon.2021.e06856
|View full text |Cite
|
Sign up to set email alerts
|

Ballistic performance of Polycarbonate and Polymethyl methacrylate under normal and inclined dynamic impacts

Abstract: Polymeric materials have exceptional mechanical properties, making them attractive for automotive, aerospace, defence and buildings industries. The numerical analysis of translucent polymeric materials' ballistic performance is investigated to analyse the deflection and perforation performance at high impact velocities. Computational methods are exploited to predict the ballistic performance of thick targets and projectile damage, and the results are validated against published works. The 3D numerical analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Molecular weight is a key parameter that affects the physical, mechanical, and processable properties of polymers, and directly determines the application of the product, as well as PC. For example, low-molecular-weight PC is suitable as a substrate for digital storage media [ 5 ], and high-molecular-weight PC with excellent optical properties is used in aircraft windshields [ 6 ] and bulletproof shields [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Molecular weight is a key parameter that affects the physical, mechanical, and processable properties of polymers, and directly determines the application of the product, as well as PC. For example, low-molecular-weight PC is suitable as a substrate for digital storage media [ 5 ], and high-molecular-weight PC with excellent optical properties is used in aircraft windshields [ 6 ] and bulletproof shields [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in order to obtain reliable impact resistance results, the test period is long. In addition, most impact studies on police riot suits are conducted for impact performance test of specific single material, [2][3][4][5] but lack of impact performance test of multi-layer series stacked products. 6 In this paper, ABAQUS is used to establish a numerical model of low energy impact of multi-layer material series stacked riot suit.…”
Section: Introductionmentioning
confidence: 99%
“…However, as stated in reference [ 20 ], this model is not very accurate in capturing the polymer yield stress at high strain rates. In this regard, other constitutive models, such as the Drucker–Prager model, which considers the pressure dependency of the polymer, were proposed by some research studies [ 21 ], or the Johnson–Cook law, which was validated on PC panels by Sarıkaya et al [ 22 ] and defines an experimental and numerical protocol for the identification of all the parameters of the model. Other advanced material models were developed for thermoplastics, as in Bergström and Bischoff’s work [ 23 ], where it was found that traditional metal plasticity models are not accurate for predicting the deformation of ultra-high molecular weight polyethylene (UHMWPE).…”
Section: Introductionmentioning
confidence: 99%